NEW DATA ON ORE MINERALOGY OF THE AK-SUG PORPHYRY Au-Mo-Cu DEPOSIT (NORTHEASTERN TUVA) - M.V. Shadchin; G.I. Shvedov; V.A. Makarov; B.M. Lobastov; S.A. Silyanov; S.S. Serdyuk (Минералогия)
New data on ore mineralogy of the Ak-Sug porphyry Au-Mo-Cu deposit (Northeastern Tuva) are presented as a result of study of ore composition using optical and scanning electron microscopy. Previously unknown minerals of Se (bohdanowiczite and berzelianite), Co (carrollite and Co-bearing pyrite), Bi (native bismuth, wittichenite, volynskite, and miharaite), Cu and Ag (mckinstryite and stromeyerite), W (scheelite), and U (brannerite) are found in ores of the deposit. The analysis of new mineral assemblages allowed us to significantly expand the list of minerals found at this deposit. The characterized minerals formed in a wide range of temperatures during several successive stages of ore formation: porphyry (carrolite and Cobearing pyrite), epithermal and subepithermal (miharaite, volynskite, wittichenite, native bismuth, Se-bearing galena). Brannerite, berzelianite, bohdanowiczite, stromeyerite, mckinstryite, and scheelite formed at the late low-temperature stage.